"He esperado", "he vuelto" y "he vivido": su valor semántico en el español de México - García Fajardo, Josefina (El Colegio de México, 2011)
This paper, which attempts to build on the previous work of other authors,studies empirical data with the aim of identifying the semantic value ofSpanish constructions such as he esperado, he vuelto, and he vivido, as they areused in Mexico. The analysis is based on the relationship that exists betweencontextual interpretations and the semantic value. In order to argue the caseof the adequacy of the semantic value proposed, this semantic value will beshown to explain the variation in contextual interpretations, and it is suggestedthat this semantic value might have been the basis for an extentionaluse that has developed in continental Spain.